An Improved Control Strategy for a Four-Leg Grid-Forming Power Converter under Unbalanced Load Conditions. (29th August 2016) - Miveh, Mohammad Reza; Rahmat, Mohd Fadli; Mustafa, Mohd Wazir; Ghadimi, Ali Asghar; Rezvani, Alireza
Abstract : This paper proposes an improved multiloop control strategy for a three-phase four-leg voltage source inverter (VSI) operating with highly unbalanced loads in an autonomous distribution network. The main objective is to balance the output voltages of the four-leg inverter under unbalanced load conditions. The proposed control strategy consists of a proportional-integral (PI) voltage controller and a proportional current loop in each phase. The voltage controller and the current control loop are, respectively, used to regulate the instantaneous output voltage and generate the pulse width modulation (PWM) voltage command with zero steady-state tracking error and fast transient response. A voltage decoupling feedforward path is also used to enhance the system robustness. Since the outer voltage loop operates in the synchronous reference frame, tuning and stability analysis of the PI controller is far from being straightforward. In order to cope with this challenge, the stationary reference frame equivalent of the voltage controller in the rotating frame is derived. Subsequently, a systematic design based on a frequency response approach is provided. Simulation results are also carried out using the DIgSILENT PowerFactory software to verify the effectiveness of the suggested control strategy.